Hubungan Sosial Ekonomi dan Perilaku Food Waste Rumah Tangga dengan Kejadian Stunting pada Balita di Desa Blimbing Kecamatan Gatak Kabupaten Sukoharjo - Nansha, Aisyah Sekar Widya; Mustikaningrum, Fitriana; Firmansyah, Firmansyah (Universitas Tadulako, 2025)
Stunting is categorized as one of the most common undernutrition problems experienced by the toddler population. Various factors, such as socioeconomic factors including education level, type of employment, and parental income as well as household food waste behavior, have a close relationship with stunting cases in toddlers. The purpose of this study was to determine the relationship between socioeconomic factors and household food waste behavior with stunting cases in toddlers in Blimbing Village, Gatak District, Sukoharjo Regency. This study used a cross-sectional research design with 63 respondents based on Lemeshow calculations taken through a simple random sampling method. Socioeconomic data including education, employment, and income were collected through questionnaires filled out directly by respondents. Data on household food waste behavior and Z-Score data were collected to measure the score and nutritional status based on height/age in toddlers. Data analysis will be conducted using the Chi-Square test, followed by the Fisher Exact Test will be applied as an alternative test. The results of the bivariate analysis between socioeconomic variables (mother's/father's education, mother's/father's occupation, income) with the incidence of stunting showed p-values ​​(p=0.177), (p=1.000), (p=0.522), (p=1.000) and (p=0.260) and household food waste behavior obtained a value (p=1.000). The conclusion in this study is that there is no relationship between socioeconomic and household food waste behavior with the incidence of stunting in toddlers in Blimbing Village, Gatak District, Sukoharjo Regency.